Grading Women's Clothing Patterns with the CAD Pattern System to Improve Student Learning Outcomes and Competencies - Kulsum, Umi (Journal of Education Technology, 2020)
The purpose of this study is to improve the quality of learning by improving student learning outcomes and competence in grading women’s fashion patterns using the CAD Pattern System learning media. The design of this study is Classroom Action Research. This research was conducted in two cycles, in each cycle consisting of four stages, namely planning, implementation, observation, and reflection. The subjects in this study were students of grade XI Fashion 1 State Vocational School 5 Malang totaling 34 students. Data collection by tests, and performance tests (performance). The results showed an improvement in student learning outcomes and competence in grading women’s fashion patterns. From the aspect of knowledge, an increase in the average score from cycle I to cycle II was 17.0. From the aspect of skills/competence, an increase in average score from cycle I to cycle II was 1.03. This study concludes that the use of the CAD Pattern System learning media is very effective, indicated by (1) improvement in student learning outcomes in making women’s fashion patterns grading, (2) improvement of student learning competence in making women's fashion patterns grading, (3) CAD Pattern System is expected to be used as a learning medium in the subjects of Industrial Clothing Making, in pattern grading competencies fashion, but still pay attention to school conditions and the characteristics of students.